Ultrasonographic methods for evaluation of testicles in cats - Brito, Marina Botelho [UNESP]; Maronezi, Marjury Cristina [UNESP]; Uscategui, Ricardo A.R. [UNESP]; Avante, Michelle L. [UNESP]; Simões, Ana R. [UNESP]; Monteiro, Frederico O.B.; Feliciano, Marcus A.R. [UNESP] (Universidad de Cordoba, 2018)
The testicles are the primary sexual organs of male and their function is to produce sperm and sexual hormones. Disorders of the testicles are common in domestic cats. Therefore, detailed assessment of the testes is of great importance in veterinary medicine. Considering the recent advances in diagnostic imaging in companion animals, this review aims to describe the applicability elastography (qualitative and quantitative), Doppler, contrast-enhanced ultrasonography and B-mode ultrasonography in testes evaluation in cats. B-mode ultrasonography of the testicles combined with haemodynamic analysis in real time by Doppler and contrast enhanced ultrasonography can assist as diagnostic tool in evaluating testicular abnormalities in sick cats. Furthermore, ARFI elastography is a new ultrasound method that evaluates tissue elasticity by elastogram and shear weave. Ultrasonographic study of the testes is a common diagnostic imaging procedure.

Los testículos son los principales órganos sexuales de los machos y su función es producir espermatozoides y hormonas sexuales. Los trastornos de estos órganos son comunes en gatos domésticos. La ultrasonografía convencional, combinada con el análisis hemodinámico en tiempo real por Doppler y ultrasonido contrastado son herramientas diagnósticas importantes para la evaluación de enfermedades testiculares en gatos. Además, La elastografía-ARFI es un método ecográfico actual que evalúa la elasticidad tisular por medio del elastograma y de la velocidad de propagación de las ondas de cizallamiento. El estudio ecográfico de los testículos es un procedimiento de diagnóstico por imágenes común.
Keywords: Doppler; Doppler Ultrasonography; Elastografia; Elastography; Testes (Source: MeSH); Testículos; Ultrasonido contrastado (Fuente: MeSH)